1994
DOI: 10.1111/j.1570-7458.1994.tb01775.x
|View full text |Cite
|
Sign up to set email alerts
|

The responses of Praon spp. parasitoids to aphid sex pheromone components in the field

Abstract: In autumn 1991, aphid parasitoids of the genus Praon (Hymenoptera; Braconidae) were caught in water traps with lures containing synthetic aphid sex pheromone components at three sites in England and one in Germany. At two of the English sites and at the German site, the traps were placed in winter cereal fields whilst the third English site was in woodland. Three species were caught, P. volucre, P. dorsale and P. abjectum. Those caught in cereal fields were almost entirely P. volucre, whilst P. dorsale dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The sexual female attracts the winged male by releasing a sex pheromone, the main chemical components of which have been identified as (4a S , 7 S , 7a R )‐nepetalactone and (1 R , 4a S , 7 S , 7a R )‐nepetalactol (Fig 1). 7, 8 It was discovered that these compounds could be obtained from a species of catmint, Nepeta cataria L,9 and in early field trials with the plant‐derived pheromone, it appeared to attract female aphid parasitoids from the genus Praon 10–12. Subsequent laboratory studies, involving electrophysiology13 and behavioural bioassays6, 14, 15 confirmed that females of a range of aphid parasitoid species showed strong responses to chemical components of aphid sex pheromones, especially to (4a S , 7 S , 7a R )‐nepetalactone.…”
Section: Parasitoid Responses To Aphid Pheromonesmentioning
confidence: 95%
“…The sexual female attracts the winged male by releasing a sex pheromone, the main chemical components of which have been identified as (4a S , 7 S , 7a R )‐nepetalactone and (1 R , 4a S , 7 S , 7a R )‐nepetalactol (Fig 1). 7, 8 It was discovered that these compounds could be obtained from a species of catmint, Nepeta cataria L,9 and in early field trials with the plant‐derived pheromone, it appeared to attract female aphid parasitoids from the genus Praon 10–12. Subsequent laboratory studies, involving electrophysiology13 and behavioural bioassays6, 14, 15 confirmed that females of a range of aphid parasitoid species showed strong responses to chemical components of aphid sex pheromones, especially to (4a S , 7 S , 7a R )‐nepetalactone.…”
Section: Parasitoid Responses To Aphid Pheromonesmentioning
confidence: 95%
“…For many aphid species, sex pheromones were identified as a mixture of two monoterpenes, (+)-(4aS,7S,7aR)-nepetalactone and (-)-(1R,4aS,7S, 7aR)-nepetalactol (Table 1), in ratios that vary according to the species (Pickett et al, 1992). These volatile compounds have been shown to attract female parasitoids in the field (Hardie et al, 1991(Hardie et al, , 1994) and elicit oriented flights by A. ervi and Aphidius eadyi Starý females when they are added to a piece of filter paper next to V. faba plants in the lab (Glinwood et al, 1999). Other examples of attraction to aphid sex pheromones include the parasitoids Praon volucre (Haliday) (Hymenoptera: Aphidiidae) and D. rapae (Gabrys et al, 1997), and the predators Chrysopa cognata McLachlan (Neuroptera: Chrysopidae) (Boo et al, 1998), and Chrysopa oculata Say (Neuroptera: Chrysopidae) .…”
Section: Habitat Locationmentioning
confidence: 99%
“…To our knowledge, naive aphid parasitoids do not respond to volatiles from plants infested by aphids. Some naive aphid parasitoids, Praon abjectum, P. dorsale, and P. volucre, are attracted by the sex pheromone of aphids, (')-(4aS, 7S, 7aR)-nepetalactone and (()-(1R, 4aS, 7S, 7aR)-nepetalactol (Hardie et al 1991(Hardie et al , 1994, and the responses of wasps to volatiles from the plant-host complex are enhanced by aphid sex pheromones (Glinwood et al 1999). In larval parasitic wasps, the response of naive wasps to the host-specific blend of volatiles is reported by Potting et al (1997).…”
Section: Response Of Naive Aphid Parasitoidsmentioning
confidence: 99%